(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Generally, infection with respiratory tract viruses leads to secondary infections in which bacteria and fungi play an important role. One of the important secondary infections related to Covid-19 is sinusitis. Due to the complications of fungal and bacterial sinusitis, it is important to know the most substantive factors that predispose people to these diseases. Covid-19 treatment solutions and excessive use of steroids and immune system of infected people are effective in causing invasive fungal sinusitis related to COVID-19. Findings show that uncontrolled blood sugar levels are also effective in sinusitis. Corona virus affects immune system. The severe inflammatory response causes an increase in cytokines and a decrease in specific immune system function in these patients and causes a prolongation of disease period and sinus tissue inflammation. Clinically, fungal and bacterial sinusitis are very similar. In this article, the aspects of corona disease and subsequent bacterial and fungal sinusitis were discussed. According to available data, a high percentage of patients with SARS-CoV-2 infection have fungal sinusitis after disease. Bacterial sinusitis is generally not as common as acute viral rhinosinusitis and affects more women than men. By attacking and causing tissue inflammation and then using corticosteroids to reduce immune response, Covid-19 provides conditions for opportunistic fungi. Often items like allergies or an acute illness like covid-19 can affect immune system. Oral corticosteroids can cause serious side effects if used long-term, so their use is recommended only when necessary and to treat severe symptoms.